Taxonomic revision of the genus Bolivaritettix Günther, 1939 (Orthoptera: Tetrigoidea: Metrodorinae) from China, with the descriptions of two new species - Deng, Wei-An; Wei, Shi-Zhen; Xin, Lei; Chen, Ya-Zhen (Zootaxa, 2018)
The tetrigid genus Bolivaritettix Günther, 1939 from China is taxonomically reviewed. The genus now includes 71 species from China, in which two new species are described and illustrated, namely: Bolivaritettix baoxingensis Deng sp. nov. and Bolivaritettix strictifemura Deng sp. nov. Synonymy. Their distribution and an annotated identification key to Chinese species are provided.